An optimal performance based new multi-objective model for heat and power hub in large scale users. (15th October 2018) - Sun, Yougang; Xu, Junqi; Lin, Guobin; Ni, Fei; Simoes, Rolando
Abstract: In recent decades, importance of green source has been increased rapidly because of these resources reduce environmental pollution and have lower operating costs. Moreover, it is possible to utilize a multi-purpose energy center scheme to provide thermal and electrical energy by the large-scale users. In this paper, we proposed a new multi-objective model based on cost-emission, operation cost of large-scale user and efficiency of electrical storage system (ESS) and thermal storage system (TSS) by considering the peak load management. This problem is solved by compromise method based on fuzzy decision making model and new Pareto filter. The main model is explained as mixed-integer linear programing and is solved by using GAMS software and CPLEX solving method. Finally, the performance of the recommended method for solving the main model is extensively explained on the two case study and compared to validate the performance of main model. Highlights: Modeling of efficiency, cost and gas release as multi-objective problem. Application of new fuzzy decision making method. Consideration of peak load management to decrease the cost and gas release.